ASSESSMENT OF THE FINANCIAL SITUATION OF COMPANIES LISTED ON THE WARSAW STOCK EXCHANGE - Szczecińska, Beata (Management and Administration Journal, 2020)
The aim of the article is to assess the financial situation of companies in the clothing and footwear sector listed on the Warsaw Stock Exchange in 2017. Firstly, financial ratios were calculated for each entity, the ranking was created and the companies were grouped in terms of their financial situation. In this way, a general picture of the competitive position of companies was obtained. The first group includes three companies with the best financial standing. They obtained the highest efficiency in the use of assets, as evidenced by the highest average values for the following stimulants: total assets turnover, current assets turnover and return on assets. Due to the fact that knowledge of financial ratios in the changing environment may be insufficient to assess the financial standing of enterprises, the weighted average cost of capital (WACC) with their components was calculated for them, which allowed judging the assessment of the structure of financing the operations of individual companies and the comparison with the financial situation determined on the basis of indicators. The best financing structure for their activities is held by companies that have been classified in high positions in a ranking based on financial indicators. However, there was one exception, which confirms the need to use different methods to assess the financial situation.